2020
DOI: 10.1016/j.jinsphys.2020.104159
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of pheromone on olfactory learning and memory in moths

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…This study showed that the sex pheromones can play modulatory roles in gustatory perception in non-social insects, such as moths, and may affect their behavioral plasticity. Follow up studies by Murmu et al [ 126 ] showed that pheromones facilitated both appetitive and aversive olfactory learning in A. ipsilon moths. The exposure to the A. ipsilon conspecific sex-pheromone before conditioning enhanced appetitive but not aversive learning, while exposure to a heterospecific sex-pheromone component facilitated aversive but not appetitive learning.…”
Section: Mechanisms Of Insect Sex Pheromone Perceptionmentioning
confidence: 99%
“…This study showed that the sex pheromones can play modulatory roles in gustatory perception in non-social insects, such as moths, and may affect their behavioral plasticity. Follow up studies by Murmu et al [ 126 ] showed that pheromones facilitated both appetitive and aversive olfactory learning in A. ipsilon moths. The exposure to the A. ipsilon conspecific sex-pheromone before conditioning enhanced appetitive but not aversive learning, while exposure to a heterospecific sex-pheromone component facilitated aversive but not appetitive learning.…”
Section: Mechanisms Of Insect Sex Pheromone Perceptionmentioning
confidence: 99%
“…Pheromones do more than conveying specific messages to members of the same species. In insects, for instance, they can modulate in the long term responsiveness to relevant stimuli (appetitive, aversive) in contexts that differ from the one for which the pheromone is used as a messenger (Baracchi et al 2017;Rossi et al 2018;Hostachy et al 2019;Rossi et al 2019;Baracchi et al 2020;Murmu et al 2020;Oberhauser et al 2020;Rossi et al 2020). Further studies are needed to clarify these novel functions of pheromones as neuromodulators and to understand their implications for the functioning of recognition systems in general.…”
Section: Discussionmentioning
confidence: 99%
“…Habituation is the simplest type of learning behavior in the animal world and refers to the gradual decay of a behavioral reaction during continuous or repeated simulation [16]. The habitual response of insects does not mean acquisition of new responses but refers to repeated contact with some stimulation that decreases the response to that stimulation, and in some cases, specific responses disappear [17,18]. After repeatedly experiencing the mixture of willow and A. chinensis fecula and wood meal at 4 days old, 6 days old, and 8 days old, instead of increasing, the tropism of these adults to odor decreased significantly compared with that of 4-day-old, 6-day-old, and 8-day-old adults that only experienced no obvious cumulative effect of repeated stimulation on learning.…”
Section: Effects Of Continuously Repeated Experience Of the Same Stim...mentioning
confidence: 99%